Understanding sleep habits and associated factors can help to improve sleep in high school adolescents - Yılmaz, Kutluhan; Kılınçaslan, Ayşe; Aydın, Neriman; Kul, Seval (The Turkish Journal of Pediatrics, 2011)
We aimed to describe the sleep profiles and associated factors of poor sleep in adolescents. We gave a sleep questionnaire and Strengths and Difficulties Questionnaire to 3,441 high school adolescents (15-18 years) in Gaziantep, Turkey. Adolescents reported a requirement of 10.4 hours of sleep on average to feel their best during the day. However, total night sleep time (TNST) was 7.42 +/- 1.48 hours on school nights and 9.40 +/- 1.37 on non-school nights. TNST of > or =9 hours on both school nights and non-school nights was detected in 8.2%. Average bedtime and wake-up time were 23:16 and 06:41 on school nights. Bedtime was approximately 30 minutes later on non-school nights. The shift in wake-up time was nearly 2.5 hours. Statistical analysis by logistic regression model showed that TNST was most significantly correlated with school start time (morning versus afternoon) irrespective of school or non-school nights. TNST on school nights was negatively correlated with age, passive smoking at home, drinking tea/coffee, and conduct problem, whereas TNST on non-school nights was negatively correlated with the mother’s education, male gender, body mass index, number of household members, and having a television in the bedroom. Daytime napping (21.3%) was associated with morning start time, age, female gender, and mother’s education. Sleep-onset insomnia with sleep latency >30 minutes (21%) was not related to age or gender; however, it was associated with abnormal breathing during sleep. The findings revealed that inadequate sleep is quite prevalent among high school adolescents. Given the fact that most of the associated factors are modifiable, inadequate sleep is not inevitable for adolescents.